COVID-19 affected elite track-and-field athletes` Olympic preparation before Tokyo 2020 compared to Rio 2016 - Banning, A.; van Meurs, E.; Dreiskämper, D. (Scientific Reports, 2025)
The COVID-19 pandemic has had a significant impact on elite sport by postponing the Olympic Games Tokyo 2020 four months before the original start. This impacted athletes` macro-cycle periodization, psychological stressors and resources. We analyse whether track-and-field athletes were able to maintain their performance levels successfully across the last two Olympic cycles, controlling for age, gender and doping prevalence. For this, worldwide competition results (excluding multi-events & relays) of at least national level since London 2012 and up to Tokyo 2020 were retrieved. Individual performance curves were analysed using hierarchical multilevel modelling. Individual baselines (random intercept) and developments (random slope) were analysed. 2,383 athletes (52% male) recorded 15,766 outcomes since London 2012. The final conditional growth model (ICC = 48%) shows that performances increased in the wake of Olympic games, dropped significantly in 2020 and recovered beyond previous form in 2021. There was no significant difference between men`s and women`s developments. Age was a significant predictor (b = 0.17, SE = 0.02), but doping violations was not (b = 0.01, SE = 0.03). These results showcase performance trends in international athletics and their variability, present an overall successful periodization to achieve peak performance at Tokyo 2020, and discuss predictions for track and field at Paris 2024.